Legal status of a disabled person in executive penal proceedings - Mieczysław Oliwa (Probacja, 2023)
This article discusses the problem of the position of a disabled person appearing in executive criminal proceedings. Due to the wide range of topics concerning both the disability itself and the rights and obligations of people with disabilities in various aspects of life, the author focuses on issues related to the position of a disabled person in the course of executive proceedings. In particular, the considerations concern the access of a disabled person, including a convicted disabled person, to a court, understood not only as a constitutional right, but also the use and access to a building intended for the needs of the judiciary. Due to not only domestic, but also international legal regulations introducing solutions in the field of enabling and facilitating the effective participation of disabled persons in conducted proceedings, the situation of disabled persons as parties to enforcement proceedings has significantly improved in terms of securing their rights and obligations. This is manifested in particular by better access for people with disabilities to buildings, signage in buildings in Braille and in forms easier to read and understand, and finally by providing assistance from officials and employees as well as other people, including professional representatives or sign language interpreters.